2013
DOI: 10.1080/09297049.2013.832741
|View full text |Cite
|
Sign up to set email alerts
|

Parenting, corpus callosum, and executive function in preschool children

Abstract: In this longitudinal population-based study (N = 544), we investigated whether early parenting and corpus callosum length predict child executive function abilities at 4 years of age. The length of the corpus callosum in infancy was measured using postnatal cranial ultrasounds at 6 weeks of age. At 3 years, two aspects of parenting were observed: maternal sensitivity during a teaching task and maternal discipline style during a discipline task. Parents rated executive function problems at 4 years of age in fiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

5
37
3
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 60 publications
5
37
3
4
Order By: Relevance
“…9 Likewise, influences of poor maternal parenting behaviors are comparable to those of postnatal maternal depression and include negative emotionality, 12 dysregulation of the stress responses, 13, 14 and poorer child behavior and socio-emotional function. 15, 16, 17, 18, 19, 20, 21, 22 Both maternal depression and parenting behaviors shape emotional and cognitive information, which affects child development in attention and memory as well as emotional reactivity of the central nervous system. 23 Nevertheless, limited research has investigated whether both independently or interactively influence child brain development, especially for brain regions associated with emotion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 Likewise, influences of poor maternal parenting behaviors are comparable to those of postnatal maternal depression and include negative emotionality, 12 dysregulation of the stress responses, 13, 14 and poorer child behavior and socio-emotional function. 15, 16, 17, 18, 19, 20, 21, 22 Both maternal depression and parenting behaviors shape emotional and cognitive information, which affects child development in attention and memory as well as emotional reactivity of the central nervous system. 23 Nevertheless, limited research has investigated whether both independently or interactively influence child brain development, especially for brain regions associated with emotion.…”
Section: Introductionmentioning
confidence: 99%
“…31 Maternal sensitivity is found to predict a variety of childhood socio-emotional constructs. 15, 16, 17, 18, 19, 20, 21, 22 This includes attachment security, a construct reflective of whether infants manage distress by approaching or avoiding their mothers. 32, 33 Maternal sensitivity, may also be expected to influence offspring affective experience, as well as their approach-avoid patterns, which may shape the neural systems supporting approach.…”
Section: Introductionmentioning
confidence: 99%
“…Considerable research demonstrates the positive impact of a healthy parent–child relationship on child development. Indeed, healthy parenting predicts greater cognitive functioning (Kok et al., ), improved emotion regulation (Manzeske & Stright, ), and increased brain gray matter volume in children (Kok et al., ). Recent studies have shown that healthy parenting during childhood may be protective against the development of emotional psychopathology (Lima et al., ; Lima, Mello, & Mari, ).…”
Section: Introductionmentioning
confidence: 99%
“…Sensitive parental care, characterized by prompt and adequate response to the child's signals and needs, 15 predicts a more secure attachment relationship, 16 higher levels of cognitive competence, 17,18 and fewer psychological problems. 19,20 The association between sensitivity and more favorable outcomes in children has been demonstrated for both mothers and fathers.…”
mentioning
confidence: 98%